Multiobjective optimisation of passive energy saving strategies in Zhuangke dwellings in Huangyuan county, China - Yunfei Liu; You Chen; Linjie Yang; Danqiu He; Muhamad Azhar Ghazali (Scientific Reports)
Abstract In rural areas of Huangyuan County, Qinghai Province, traditional dwellings are gradually being replaced by self-built brick-concrete houses that mimic urban designs, leading to increased energy consumption and reduced indoor thermal performance. This issue is particularly urgent in economically disadvantaged regions with harsh climatic conditions. Traditional Zhuangke dwellings, however, feature architectural characteristics that are well-suited to the cold climate and limited local resources. Extracting and optimising the passive energy-saving design of these traditional dwellings presents an effective solution to address the conflict between energy efficiency and indoor thermal performance in self-built rural houses. This study Innovatively develops a multi-objective optimisation framework for passive energy-saving design in rural housing in Huangyuan County, using the Rhino and Grasshopper visual programming platform. The framework aims to resolve this conflict. By analysing the design parameters of 53 traditional Zhuangke dwellings, the study optimises 10 passive energy-saving design parameters, including courtyard length, width, building orientation, height, depth, span, ground clearance, window-to-wall ratio, sunroom depth, and north-facing double-wall cavity depth. The Technique for Order Preference by Similarity to Ideal Solution​ (TOPSIS) method is then applied to filter the Pareto optimal solutions. The results show that, compared to the baseline building, the optimised “linear courtyard” Zhuangke dwelling achieves a reduction in heating energy use intensity (EUI) by 1–17.9% and an improvement in indoor standard effective temperature (SET) ranging from 4.1 to 5.4%. This study provides quantitative evidence and practical design strategies tailored to linear courtyard-type Zhuangke dwellings in rural Qinghai, contributing to the reduction of heating energy consumption and the improvement of indoor thermal performance in cold-climate self-built housing.